TELEVISI SEBAGAI MEDIA DAKWAH - Arif Arif; Samsinas Samsinas; Mansur Mangasing (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
Islam is one of the divine religions that emphasizes the importance of da’wah (Islamic preaching) activities. Therefore, da'wah becomes one of the activities of every Muslim in his life. Da’wah can be done through various ways and media, both visual and audio visual, such as television and others. Television is very effective in delivering content of da’wah, because in this modern era television has been entering in almost all the homes of the people as audiences of da’wah. The most important is to display the right content with competent speakers, and with the right program or event as well. In this case, Televisi Republik Indonesia (TVRI) Central Sulawesi created a program called Lentera Hati. This is a program of Islamic da’wah that is broadcasted on every Thursday at 20.00 pm. The content is delivered through the presentation of the material by a competent speaker. Thus, the goal of da’wah to the people of Central Sulawesi as audiences can be achieved.